(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The horned carp, Schismatorynchos nukta (Sykes, 1839) has been recorded for the first time from Bangladesh geographical area under the investigated genus of Schismatorynchos (Bleeker 1855). This fish was collected from seine net catch while exploring the hilly upstream of Sangu river at Tindu and Remakri (Thanchi, Bandarban, Bangadesh) during the winter in 2015. The species S. nukta is mostly distributed in the upland tributaries of Krishna river systems at northern Western Ghats, Maharashtra and Karnataka in India. It is reported as endemic species of Western Ghats biodiversity hotspot. Its distribution (IUCN status) and habitat conditions are dealt in the present paper. The findings add some information on its global distribution form and Indian endemic status. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(1): 85-92